PERAN PEMERINTAH DESA DALAM PENGAWASAN PERTAMBANGAN EMAS RAKYAT DI DESA RATATOTOK KABUPATEN MINAHASA TENGGARA - Mantiri, Jeane; Langkai, Erica; Mamonto, Fitri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Unlicensed small-scale gold mining (PETI) has become a critical issue in Ratatotok Village, Southeast Minahasa Regency. While this activity benefits residents economically, it also causes environmental degradation and social conflicts. This study explores the village government's role in supervising community-based gold mining practices. A qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings reveal that the village government's oversight is still passive and suboptimal. The main obstacles are limitations in authority, a lack of regulatory socialization, and weak inter-institutional coordination. Due to social pressure and limited resources, the village government struggles to take decisive action against illegal mining. Therefore, enhancing the capacity of village governance, strengthening collaboration with law enforcement agencies, and promoting public awareness are crucial for fostering legal and sustainable small-scale mining governance